Impact of complex congenital heart disease on the prevalence of arterial hypertension after aortic coarctation repair. (6th August 2018) - Giordano, Ugo; Chinali, Marcello; Franceschini, Alessio; Cafiero, Giulia; Yammine, Marie Laure; Brancaccio, Gianluca; Giannico, Salvatore
Abstract: OBJECTIVES: This study was designed to evaluate the difference in the prevalence of long-term arterial hypertension among patients with corrected aortic coarctation according to the existence of associated cardiac congenital lesions. METHODS: We identified 235 patients who had undergone surgery for aortic coarctation and classified them into 2 groups: patients with isolated coarctation of the aorta (CoA) and patients with aortic coarctation associated with complex congenital heart disease. Data were retrospectively analysed. RESULTS: There were 148 subjects with isolated CoA and 87 with complex CoA (CoA-c). Patients were defined as hypertensive if they required antihypertensive treatment and/or when blood pressure was above 95th percentile. Patients with isolated aortic coarctation were significantly younger than patients with CoA-c ( P < 0.001) and a markedly higher prevalence of arterial hypertension (44% vs 24%) was documented in the isolated coarctation group. The difference in the prevalence of hypertension in the 2 groups was still significant after correcting for differences in age ( P < 0.001), confirming that the prevalence of arterial hypertension in patients with CoA-c was half of that of patients with isolated CoA. CONCLUSIONS: We conclude that complex congenital heart disease in patients who have undergone surgical correction for aortic coarctation results in a significantly lower prevalence of late-onset hypertension. Reduced systemic flow and pressure before surgery in patients with CoA-c might be associated with a lower rate of arterial hypertension.